Sustainable Banking Institutional Collaboration in Pension Account Decisions - Danang Andi Wijanarko; Zaenal Arifin; I Made Sukresna (Arthatama: Journal of Business Management and Accounting, 2025)
The transformation of the financial system in Indonesia has created opportunities for the development of more inclusive and sustainable banking services, especially for the workforce approaching retirement. This study aims to analyze how trust, accessibility, and institutional collaboration influence individual decision-making in selecting retirement accounts. Using a qualitative approach, the research explores the perceptions and subjective experiences of workers nearing retirement through in-depth interviews, participatory observation, and focus group discussions. The findings reveal that trust in the reputation and integrity of financial institutions, ease of access to both physical and digital banking services, and collaboration between employers and banks are dominant factors influencing financial decisions during the transition to retirement. These results highlight the importance of enhancing financial literacy, developing adaptive retirement products, and providing more personalized and responsive services as part of an inclusive sustainable banking strategy for the elderly workforce. Strengthening these aspects will support a more effective and inclusive approach to retirement planning, benefiting the aging population in Indonesia.